Dopamine-modified carboxymethyl cellulose as an improved aqueous binder for silicon anodes in lithium-ion batteries. (1st September 2021) - Wang, Zechen; Huang, Tao; Liu, Zhaolin; Yu, Aishui
Abstract: The intractable issues of silicon anodes hinder its wide application in high-capacity Li-ion batteries. Binders are proven to be one of the effective ways to enhance the electrochemical performance of Si anodes. Inspired by mussels, the water soluble binder carboxymethyl cellulose (CMC) is modified through amidation reaction, and the dopamine moieties are successfully introduced into the polymer backbone of CMC. The dopamine-modified CMC (CMC-DOP) is confirmed by liquid 1 H nuclear magnetic resonance ( 1 H NMR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) techniques. The CMC-DOP with polar catechol groups and affluent anchoring points exhibits higher adhesive force and superior electrochemical performance. The Si @ CMC-DOP electrode delivers a high initial specific capacity of 3418.2 mAh g −1 and maintains satisfactory capacity of 1650.6 mAh g −1 after 200 cycles. Furthermore, the tight wrapping/coating effect of CMC-DOP binder can effectively protect the active material from exposure to electrolyte, and reduce the decomposition of electrolyte as well as the massive formation of solid electrolyte interface (SEI) layers. The Si electrode with CMC-DOP binder shows slight polarization and intact structure in long-term cycling. Graphical abstract: Image, graphical abstract